CUSTOMER SATISFACTION ANALYSIS BY RECENT ARTIFICIAL INTELLIGENCE TECHNOLOGY PLATFORMS - Jaideep Dutta, Dr. Swati Saxena (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The second era of marketing, started after 1960s, is known as the sales era. During this era, product supply exceeded demand. Thus, firms assumed that consumers would resist buying goods and services deemed nonessential. To overcome this consumer resistance, sellers had to employ creative advertising and skillful personal selling in order to get consumers to buy. The marketing era emerged after firm managers realized that a better strategy was needed to attract and keep customers because allowing products to sell themselves was not effective. Rather, the marketing concept philosophy was adopted by many firms in an attempt to meet the specific needs of customers. Proponents of the marketing concept argued that in order for firms to achieve their goals, they had to satisfy the needs and wants of consumers. The third era of marketing started after 1990s, is known as the strategic concept of marketing. During this era the focus of marketing shifted from the customer or the product to the customer in the context of the broader external environment. Knowing everything about the customer is not enough. To succeed, marketers must know the customer in a context including the competition, government policy & regulation, and the broader economic, social and political macro forces that shape the evolution of markets. In global marketing this may mean working closely with home country government trade negotiators and other officials and industry competitors to gain access to a target country market.